Study on Optimization of Delay Method of Wedge Cut Blasting in Tunnel - Wenle Gao; Zhicheng Liu; Yanping Wang; Zhenwei Yan; Zehua Zhang (Shock and Vibration)
Relying on the entrance section of a high-speed railway tunnel blasting project, the fluid-solid coupling algorithm based on ANSYS/LS-DYNA was used to optimize the parameters of wedge cut blasting, and the vibration could be reduced on the basis of ensuring the blasting effect. Through the combination of visual numerical simulation results and rock-breaking mechanism of wedge cut blasting, the maximum vibration velocity of different monitoring points in the model under different segmented time delay was analyzed. The results show that the best method for detonation is dividing the blastholes into three segments from upper to lower and dividing the left and right symmetrical blastholes into one segment. When the delay time is 10 ms, the average vibration reduction ratio is the best, which is reduced by 18% compared with the six-hole simultaneous blasting. In addition, the actual surrounding rock stress has a clamping effect on the cut blasting area. The wedge cut blasting footage obtained by numerical simulation was basically consistent with the field results, which proved that the model is reasonable and effective. This study intuitively and accurately demonstrated the process of cut blasting, the superposition curve of vibration velocity and the vibration reduction results under different delay times, and the effect of cut blasting. The results can be directly applied to similar projects, and the optimal blasting parameters and related issues can be solved more accurately with the help of this engineering analysis method.